Engineering students' and faculty perceptions of teaching methods and the level of faculty involvement that promotes academic success - Karpilo, Lacy N., author; Lehmann, Jean, advisor; Siller, Tom, advisor (Colorado State University. Libraries, 2008)
Student academic success is a top priority of higher education institutions in the United States and the trend of students leaving school prior to finishing their degree is a serious concern. Accountability has become a large part of university and college ratings and perceived success. Retention is one component of the accountability metrics used by accreditation agencies. In addition, there are an increasing number of states allocating funds based in part on retention (Seidman, 2005). Institutions have created initiatives, programs, and even entire departments to address issues related to student academic success to promote retention. Universities and colleges have responded by focusing on methods to retain and better serve students. Retention and student academic success is a primary concern for high education institutions; however, engineering education has unique retention issues. The National Science Board (2004) reports a significant decline in the number of individuals in the United States who are training to become engineers, despite the fact that the number of jobs that utilize an engineering background continues to increase. Engineering education has responded to academic success issues by changing curriculum and pedagogical methods (Sheppard, 2001). This descriptive study investigates the perception of engineering students and faculty regarding teaching methods and faculty involvement to create a picture of what is occurring in engineering education. The population was the engineering students and faculty of Colorado State University's College of Engineering. Data from this research suggests that engaging teaching methods are not being used as often as research indicates they should and that there is a lack of student-faculty interaction outside of the classroom. This research adds to the breadth of knowledge and understanding of the current environment of engineering education. Furthermore, the data allows engineering educators and other higher education professionals to gain insight into the teaching methods currently being utilized in engineering and reinforces the importance of student-faculty interaction and thus facilitating the creation of programs or initiatives to improve student academic success.
Keywords: academic success; engineering students; faculty involvement; teaching; school administration; science education; curriculum development; higher education; educational administration